A contemporary understanding of iron metabolism in active premenopausal females - Badenhorst, Claire E.; Forsyth, Adrienne K.; Govus, Andrew D. (Frontiers in Sports and Active Living, 2022)
Iron metabolism research in the past decade has identified menstrual blood loss as a key contributor to the prevalence of iron deficiency in premenopausal females. The reproductive hormones estrogen and progesterone influence iron regulation and contribute to variations in iron parameters throughout the menstrual cycle. Despite the high prevalence of iron deficiency in premenopausal females, scant research has investigated female-specific causes and treatments for iron deficiency. In this review, we provide a comprehensive discussion of factors that influence iron status in active premenopausal females, with a focus on the menstrual cycle. We also outline several practical guidelines for monitoring, diagnosing, and treating iron deficiency in premenopausal females. Finally, we highlight several areas for further research to enhance the understanding of iron metabolism in this at-risk population.